Nursing Activities Score: an updated guideline for its application in the Intensive Care Unit - Katia Grillo Padilha; Siv Stafseth; Diana Solms; Marga Hoogendoom; Francisco Javier Carmona Monge; Om Hashem Gomaa; Konstantinus Giakoumidakis; Margarita Giannakopoulou; Maria Cecília Gallani; Edyta Cudak; Lilia de Souza Nogueira; Cristiane Santoro; et al. (SciELO, 2015)
ABSTRACT Objective To describe nursing workload in Intensive Care Units (ICU) in different countries according to the scores obtained with Nursing Activities Score (NAS) and to verify the agreement among countries on the NAS guideline interpretation. Method This cross-sectional study considered 1-day measure of NAS (November 2012) obtained from 758 patients in 19 ICUs of seven countries (Norway, the Netherlands, Spain, Poland, Egypt, Greece and Brazil). The Delphi technique was used in expertise meetings and consensus. Results The NAS score was 72.8% in average, ranging from 44.5% (Spain) to 101.8% (Norway). The mean NAS score from Poland, Greece and Egypt was 83.0%, 64.6% and 57.1%, respectively. The NAS score was similar in Brazil (54.0%) and in the Netherlands (51.0%). There were doubts in the understanding of five out 23 items of the NAS (21.7%) which were discussed until researchers' consensus. Conclusion NAS score were different in the seven countries. Future studies must verify if the fine standardization of the guideline can have a impact on differences in the NAS results.